Data Resource Profile: The Age-It Family Demography Survey (Age-It FDS) - Vignoli, Daniele; Brini, Elisa; Guetto, Raffaele; Alderotti, Giammarco; Ballerini, Andrea; Cozzani, Marco; Gallo, Alessandro; Gil-Hernández, Carlos Javier; Morabito, Maria Francesca; Pirani, Elena; Soldati, Davide; Tata, Francesco; et al. (International Journal of Population Data Science, 2026)
Introduction Italy has recently witnessed profound transformations in family dynamics, including delayed union formation, rising cohabitation, increasing relationship instability, and postponed parenthood. These shifts have occurred alongside persistently lowest-low fertility rates and a growing use of medically assisted reproduction (MAR). Existing Italian datasets do not simultaneously capture these new family dynamics, nor do they address other emerging themes such as online dating patterns, MAR experiences and trajectories, and the forward-looking narratives through which individuals interpret uncertain futures. The Age-It Family Demography Survey (Age-It FDS), conducted within Spoke 1 of the Research Programme Age-It, is specifically designed to fill this gap. Methods The Age-It FDS is a cross-sectional, quota-controlled survey of 9,004 individuals aged 18–45 residing in Italy. Sampling followed a stratified design with quotas based on the intersection of age groups, sex, and macro-area (at NUTS-1 level), as well as independent quotas based on municipality size, educational attainment, and citizenship. Data were collected between May and July 2025 using a mixed-mode design (CAPI, CATI, CAWI), after extensive questionnaire design, piloting, and interviewer training. Results The dataset contains detailed union and childbearing histories, information on partners' characteristics across successive unions, a family complexity module, online dating, and an extensive module on MAR. A key innovation is the inclusion of narratives of the future measures, which record expectations regarding economic (in)security, employment, housing, environmental risks, political stability, and social cohesion. Data quality is supported by built-in validation routines in the computer-assisted interviewing platform (including range and consistency checks), dedicated try-out phases, and ex-post validation, including recalls and examination of non-response patterns. Conclusion The Age-It FDS provides an unprecedented resource for studying contemporary fertility and family dynamics in Italy. Data are stored at the Department of Statistics, Computer Science, Applications "G. Parenti" (DiSIA), University of Florence, available upon request to the corresponding author for non-commercial, scientific purposes.